Impact Evaluation of a Community based Water Harvesting System at Village Mandhala in Shivalik Foothills of Himachal Pradesh - Y. Agnihotri; A.K. Tiwari; Ram Murti; Surender Singh (Journal of Soil and Water Conservation, 2022)
Shivalik foothills in Himachal Pradesh are marked by frequent crop failures due to erratic rainfall, lack of irrigation facilities, serious soil erosion problem, unemployment and poverty. During the earlier days the villages of the region had their own ponds, which served the society. Over the period of time bond of the villagers over such common property is getting weak. An old silted up pond in village Mandhala (H.P.) of storage capacity 0.7 ha m was renovated under an integrated watershed management project with community participation. The newly created storage capacity of2.0 ha m of the pond now irrigates 10.0 ha of land, mostly for wheat crop. The project has resulted in increase in cropped area of27.4% during Kharifand 46.8% during Rabi season. The wheat crop which was taken earlier under rainfed condition, now gets supplemental irrigation. The yield of wheat and maize has shot up to 29.8 q/ha and 30.0 q/ha respectively over the earlier yield of 8.8 g/ha and 9.5 q/ha of the two crops before the project. The total milk yield has too got a: quantum jump of 48,056 l/annum from 37,925 I/annum earlier. The project, over the 3 years (2002-05), generated employment for 7271 man days. The programme was highly favoured by the villagers as most of them elicited the same as ‘very appropriate’ and felt ‘satisfied’ from the angle of fulfilling their needs.